Static and dynamic GPS receiver verification tests using software defined radio - Kliwati, Sri; Wiryadinata, Romi; Muttakin, Imamul; Setyawan, Haris; Rustamaji, Rustamaji; Widada, Wahyu (Jurnal Teknika, 2024)
Global Positioning System (GPS) is widely used in a variety of fields, including aircraft applications and rockets where speeds exceed standards. Signal simulators, which are relatively expensive, are required to test commercial GPS devices and GPS signal processing methods. The methodology for verifying GPS receiver specifications using a Software Defined Radio (SDR)-based simulator is described in this paper. Simulator tests are run in both static and dynamic modes. The test findings demonstrate that the system can measure altitude and speed, but only up to 50 km and 500 m/s, respectively, according to commercial GPS specifications. This simulator system can be used to evaluate future GPS processing algorithms in highly dynamic environments.